Tolerance as a Founding Value of World Peace - Pinto, Anselmo Orlando (Advances in Social Sciences Research Journal, 2024)
Societies today have a heightened awareness of their unity and the way in which each individual depends on the other in indispensable solidarity; however, within these societies bitter political, social, economic, racial and ideological disputes persist and with them the danger of a war that could jeopardize world peace. It is in this context that tolerance emerges as a fundamental ethical priority for building and maintaining peace in the world. Tolerance, therefore, does not imply neutrality of thought, on the contrary, each group has space to present their points of view and experiences for everyone's co-reflection, and everyone is asked to respect the essential norms to the functioning of pluralism. The advocacy of tolerance represents a project of emancipation and is based on the strength of human reason. The objective of this thematic proposal is to reflect on the mystery of man and the meaning of his social being through the prism of considering the moral value of tolerance in the political-democratic order and in social coexistence. Democracy, whose assumptions are condensed in the production of consensus in relation to the good of political life and the experience of citizenship, must recognize that social pluralism poses challenges to the idea of tolerance based on the ontology of the person. For a proper approach to the topic in question, which involve a triple joint: 1) The problem of intolerant democracies today; 2) Social pluralism and public security, and 3) Tolerance and world peace, priority will be given to the method of reviewing the vast and rich literature that discusses the subject in question. In conclusion, the study puts forward the thesis that in the face of various existential scenarios that negatively mark the recent history of many peoples and nations - such is the case of violent extremism in the world, electoral offenses and, consequently, barbaric demonstrations post-elections, the human-environment relationship - the moral value of tolerance continues to be an important factor in building world peace and must therefore be cultivated by everyone.